The Tidal Disruption Event AT2021ehb: Evidence of Relativistic Disk Reflection, and Rapid Evolution of the Disk-Corona System - Yao, Y.; Lu, W.; Guolo, M.; Pasham, D.R.; Gezari, S.; Gilfanov, M.; Gendreau, K.C.; Harrison, F.; Cenko, S.B.; Kulkarni, S.R.; Miller, J.M.; Walton, D.J.; et al. (IOP Publishing Ltd, 2022)
We present X-ray, UV, optical, and radio observations of the nearby (≈78 Mpc) tidal disruption event AT2021ehb/ZTF21aanxhjv during its first 430 days of evolution. AT2021ehb occurs in the nucleus of a galaxy hosting a≈107 M ⊙ black hole (M BH inferred from host galaxy scaling relations). High-cadence Swift and Neutron Star Interior Composition Explorer (NICER) monitoring reveals a delayed X-ray brightening. The spectrum first undergoes a gradual soft → hard transition and then suddenly turns soft again within 3 days at δ t≈272 days during which the X-ray flux drops by a factor of 10. In the joint NICER+NuSTAR observation (δ t = 264 days, harder state), we observe a prominent nonthermal component up to 30 keV and an extremely broad emission line in the iron K band. The bolometric luminosity of AT2021ehb reaches a maximum of 6.0 − 3.8 + 10.4 % L Edd when the X-ray spectrum is the hardest. During the dramatic X-ray evolution, no radio emission is detected, the UV/optical luminosity stays relatively constant, and the optical spectra are featureless. We propose the following interpretations: (i) the soft → hard transition may be caused by the gradual formation of a magnetically dominated corona; (ii) hard X-ray photons escape from the system along solid angles with low scattering optical depth (∼a few) whereas the UV/optical emission is likely generated by reprocessing materials with much larger column density—the system is highly aspherical; and (iii) the abrupt X-ray flux drop may be triggered by the thermal-viscous instability in the inner accretion flow, leading to a much thinner disk.